Observer-Controller Based Reference Model of Lateral Dynamics of Four-Wheel Steered Vehicles - Acosta-Barbosa, K; El Aiss-Berazouq, H (Institute of Electrical and Electronics Engineers Inc., 2024)
This article presents an observer-based control framework designed for four-wheel steering (4WS) vehicles, aimed at improving lateral stability and handling. Relying on active front/rear steering and direct yaw moment control, the system guides the vehicle to closely follow the desired lateral sideslip angle and yaw rate of the reference model. Different from previous approaches, this work takes into account longitudinal speed variations within a given range, adopting the Takagi-Sugeno (T-S) fuzzy method to deal with the resulting non-linearities and build an appropriate T-S fuzzy model. The design of the control and observer is based on the common Lyapunov function method, with stability conditions expressed as linear matrix inequalities (LMIs). Simulation results validate the effectiveness of the proposed method in achieving the main objectives of this study. © 2024 IEEE.